2023
DOI: 10.1001/jamapsychiatry.2022.5056
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Health With Risk of Clinically Relevant Depressive Symptoms

Abstract: ImportanceCardiovascular health may be used for prevention of depressive symptoms. However, data on the association of cardiovascular health across midlife with depressive symptoms are lacking.ObjectiveTo evaluate whether better baseline cardiovascular health and improvement of cardiovascular health over time are associated with a lower risk of both incident depressive symptoms and unfavorable trajectories of depressive symptoms.Design, Setting, and ParticipantsParticipants without depressive symptoms were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our results contradict the results of Caruncho and Rivera-Baltanas and what is reported by Segoviano-Mendoza et al (2018) since we found an increase in depression symptoms related to a decrease in cortisol levels and an increase in serum cholesterol levels. However, they are similar to the results of other studies, such as those of van Sloten et al (2023) , who found that having better cardiovascular health, as measured by normal cholesterol levels, exercising, and having a normal BMI are favorable factors for not experiencing depression symptoms, and those of the study by Lindqvist et al (2008) which relates variability in cortisol and symptoms of depression.…”
Section: Discussionsupporting
confidence: 89%
“…Our results contradict the results of Caruncho and Rivera-Baltanas and what is reported by Segoviano-Mendoza et al (2018) since we found an increase in depression symptoms related to a decrease in cortisol levels and an increase in serum cholesterol levels. However, they are similar to the results of other studies, such as those of van Sloten et al (2023) , who found that having better cardiovascular health, as measured by normal cholesterol levels, exercising, and having a normal BMI are favorable factors for not experiencing depression symptoms, and those of the study by Lindqvist et al (2008) which relates variability in cortisol and symptoms of depression.…”
Section: Discussionsupporting
confidence: 89%
“…They have a solid clinical basis and underpin all the CVH metrics, interacting bidirectionally. 13,20,21 Previous research has revealed that poor CVH was related to depressive symptoms 22,23 and social isolation. 24 Another study found an effect modification by CVH on the relationship between socioeconomic status and life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, CVH was not only widely employed to estimate the risks of cardiovascular events and cognitive health [9][10][11] , but also the risk of depression. Recently, a prospective community-based cohort of 6,980 participants in France found that better CVH was associated with a lower risk of depressive symptoms over time 12 . It is line with a longitudinal analysis of ELSA-Brasil included 9,214 participants also suggested that poor cardiovascular health tripled depression risk at follow-up in otherwise healthy adults 13 .…”
Section: Introductionmentioning
confidence: 99%